Comparative analysis of phase I and II enzyme activities in 5 hepatic cell lines identifies Huh-7 and HCC-T cells with the highest potential to study drug metabolism - Lin, Jie; Dooley, Steven (Archives of toxicology, 2012)
Primary human hepatocytes (hHeps) are still gold standard to perform human drug metabolism studies, but their availability is limited by donor organ scarcity. Therefore, hepatoma cell lines are widely used as alternatives, although their phases I and II drug-metabolizing activities are substantially lower compared with hHeps. The major advantage of these cell lines is immediate availability, standardized culture conditions and unlimited life span. Therefore, the aim of this study was to investigate the drug-metabolizing profile of five human hepatoma cell lines (HepG2, Hep3B, HCC-T, HCC-M and Huh-7) over a culture period of 10 passages. Fluorescent-based assays for seven different cytochrome P450 (CYP) isoforms and seven different phase II enzymes were performed and compared with enzymatic activities of hHeps. CYP activities were much lower in the cell lines (5-15% of hHeps), whereas phase II enzyme activities that are involved in buffering oxidative stress (e.g., Glutathione-S-transferase) reached levels comparable with hHeps. Furthermore, phases I and II enzyme activities in hepatoma cell lines vary strongly during culture time. Interestingly, the most constant results were obtained with Huh-7 cells. Huh-7 cells as well as HCC-T cells exhibited a drug-metabolizing profile closest to hHeps between passages two and four. Toxicity studies with Diclofenac, Paracetamol and Verapamil in both cell lines show dose-response characteristics and EC50 values similar to hHeps. Therefore, we propose that due to the more consistent results throughout the passages, Huh-7 could be an alternative system to the limitedly available hHeps and frequently used HepG2 cell line in the study of drug metabolism.